Regulation of Microglia and Macrophage Polarization via Apoptosis Signal-Regulating Kinase 1 Silencing after Ischemic/Hypoxic Injury - Cheon, So Yeong; Kim, Eun Jung; Kim, Jeong Min; Kam, Eun Hee; Ko, Byung Woong; Koo, Bon-Nyeo (Frontiers in Molecular Neuroscience, 2017)
Inflammation is implicated in ischemic stroke and is involved in abnormal homeostasis. Activation of the immune system leads to breakdown of the blood brain barrier (BBB) and, thereby, infiltration of immune cells into the brain. Upon cerebral ischemia, infiltrated macrophages and microglia (resident CNS immune cell) are activated, change their phenotype to M1 or M2 based on the microenvironment, migrate toward damaged tissue, and are involved in repair or damage. Those of M1 phenotype release pro-inflammatory mediators, which are associated with tissue damage, while those of M2 phenotype release anti-inflammatory mediators, which are related to tissue recovery. Moreover, late inflammation continually stimulates immune cell infiltration and leads to brain infarction. Therefore, regulation of M1/M2 phenotypes under persistent inflammatory conditions after cerebral ischemia is important for brain repair. Herein, we focus on apoptosis signal-regulating kinase 1 (ASK1), which is involved in apoptotic cell death, brain infarction, and production of inflammatory mediators under cerebral ischemia. We hypothesized that ASK1 is involved in the polarization of M1/M2 phenotype and the function of microglia and macrophage during the late stage of ischemia/hypoxia. We investigated the effects of ASK1 in mice subjected to middle cerebral artery occlusion and on BV2 microglia and RAW264.7 macrophage cell lines subjected to oxygen-glucose deprivation. Our results showed that ASK1 silencing effectively reduced Iba-1 or CD11b- positive cells in ischemic areas, suppressed pro-inflammatory cytokines, and increased anti-inflammatory mediator levels at 7 days after cerebral ischemia. In cultured microglia and macrophages, ASK1 inhibition, induced by NQDI-1 drug, decreased the expression and release of M1-associated factors and increased those of M2-associated factors after hypoxia/reperfusion (H/R). At the gene level, ASK1 inhibition suppressed M1-associated genes and augmented M2-associated genes. In gap closure assay, ASK1 inhibition reduced the migration rate of microglia and macrophages after H/R. Taken together, our results provide new information that suggests ASK1 controls the polarization of M1/M2 and the function of microglia and macrophage under sustained-inflammatory conditions. Regulation of persistent inflammation via M1/M2 polarization by ASK1 is a novel strategy for repair after ischemic stroke.